2020
DOI: 10.3390/atmos11040429
|View full text |Cite
|
Sign up to set email alerts
|

Improving Air Quality in the Po Valley, Italy: Some Results by the LIFE-IP-PREPAIR Project

Abstract: The Po Valley (Northern Italy) represents an important exceedance zone of the air-quality limit values for PM (particulate matter), NO2 (nitrogen dioxide) and O3 (ozone). This area covers the territory of most Italian northern regions and includes several urban agglomerates, such as Milan, Turin, Venice and Bologna. The area is densely populated and heavily industrialized. The paper summarizes the assessment of the impact of the current (2013) and future (2025) emissions and of the meteorological conditions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 8 publications
3
33
0
Order By: Relevance
“…The seasonal fields of PM 2.5 clearly show that high yearly average values mostly result from the winter season contributions when more stable atmospheric conditions lead to stagnant conditions, favouring the accumulation of particulate matter in the area (Pernigotti et al, 2014;Raffaelli et al, 2020). The increased emissions from the residential sector (heating, especially wood burning) foster this process (Ricciardelli et al, 2017;Hakimzadeh et al, 2020). Wintertime low temperatures also favour the partitioning of semi-volatile components (e.g.…”
Section: P αmentioning
confidence: 99%
“…The seasonal fields of PM 2.5 clearly show that high yearly average values mostly result from the winter season contributions when more stable atmospheric conditions lead to stagnant conditions, favouring the accumulation of particulate matter in the area (Pernigotti et al, 2014;Raffaelli et al, 2020). The increased emissions from the residential sector (heating, especially wood burning) foster this process (Ricciardelli et al, 2017;Hakimzadeh et al, 2020). Wintertime low temperatures also favour the partitioning of semi-volatile components (e.g.…”
Section: P αmentioning
confidence: 99%
“…Crude fact is that deaths from air pollution accounted for 7.6% of all fatalities worldwide as per 2016 report by WHO (WHO, 2020;Isaifan, 2020). So, such reduced pollution level could be help nature to restore herself and help people to get fresh breath (Kelly and Fussell, 2015;Wu et al, 2017;Ma et al, 2020;Yongjian et al, 2020;Sharma et al, 2020;Raffaelli et al, 2020). In China, NO 2 and carbon emissions have reduced respectively by 30 and 25% (Lauri, 2020;McMahon, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to restrain the rapid spread of this infectious pathogen, governments have adopted various prevention and control strategies such as social distancing, businesses shutdown, and city-wide lockdowns ( Anjum, 2020 ; Collivignarelli et al, 2020 ). Due to the implementation of abovementioned strategies, several recent studies have reported improvements in urban air quality, mainly attributed to the significant decreases in road traffic and (to some extent) industrial emissions ( Bao and Zhang, 2020 ; Raffaelli et al, 2020 ; Tobías et al, 2020 ). Among different criteria air pollutants, ambient fine particulate matter (PM 2.5 , particle with aerodynamic diameter <2.5 μm) is of great importance due to its distinct physio-chemical characteristics and well-established adverse health consequences (e.g., respiratory and cardiovascular disease) ( Brook et al, 2010 ; Gauderman et al, 2002 ; Pope et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%